(3cJGH aj Gdabg GdeGdcis ((3ehQjJGfjG s)
(3ChdgG (B:s
(3jHOC ef cJGH Chdg JCNjQ UdGI GdYTGA ai GdMQ eSCdI hSFd Yf GdNajf jdHSgeG GdQLd s
(3BNQgG (B:s
(3BNQ GdehLhO efg jfJgi YfO bhdg (B: (3de jcf JCNQ ENQGL GdRcGI Zdi Mjf GdeaGVdI eYfi HYO gPG s
(3GdeNWhW eaccs
(3cJHJ HYV GdYfGhjf HGdMeQIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs